Solvability and Stability of Impulsive Set Dynamic Equations on Time Scales - Shihuang Hong; Jing Gao; Yingzi Peng (Abstract and Applied Analysis)
A class of new nonlinear impulsive set dynamic equations is considered based on a new generalized derivative of set-valued functions developed on time scales in this paper. Some novel criteria are established for the existence and stability of solutions of such model. The approaches generalize and incorporate as special cases many known results for set (or fuzzy) differential equations and difference equations when the time scale is the set of the real numbers or the integers, respectively. Finally, some examples show the applicability of our results.